Comprehensive Management With the ABC (Atrial Fibrillation Better Care) Pathway in Clinically Complex Patients With Atrial Fibrillation: A Post Hoc Ancillary Analysis From the AFFIRM Trial - Proietti, Marco; Romiti, Giulio Francesco; Olshansky, Brian; Lane, Deirdre A.; Lip, Gregory Y. H. (Journal of the American Heart Association, 2020)
Background For patients with atrial fibrillation, a comprehensive care approach based on the Atrial fibrillation Better Care (ABC) pathway can reduce the occurrence of adverse outcomes. The aim of this paper was to investigate if an approach based on the ABC pathway is associated with a reduced risk of adverse events in "clinically complex" atrial fibrillation patients, including those with multiple comorbidities, polypharmacy, and prior hospitalizations. Methods and Results We performed a post hoc analysis of the AFFIRM (Atrial Fibrillation Follow-up Investigation of Rhythm Management) trial. The principal outcome was the composite of all-cause hospitalization and all-cause death. An integrated care approach (ABC group) was used in 3.8% of the multimorbidity group, 4.0% of the polypharmacy group, and 4.8%, of the hospitalized groups. In all "clinically complex" groups, the cumulative risk of the composite outcome was significantly lower in patients managed consistent with the ABC pathway versus non-ABC pathway-adherent (all <0.05). Cox regression analysis showed a reduction of composite outcomes in ABC pathway-adherent versus non-ABC pathway-adherent for multimorbidity (hazard ratio [HR], 0.61, 95% CI, 0.44-0.85), polypharmacy (HR, 0.68, 95% CI, 0.47-1.00), and hospitalization (HR, 0.59, 95% CI, 0.42-0.85) groups. Secondary analyses showed that the higher number of ABC criteria fulfilled the larger associated reduction in relative risk, even for secondary outcomes considered. Conclusions Use of an ABC consistent pathway is associated with fewer major adverse events in patients with atrial fibrillation who have multiple comorbidities, use of polypharmacy, and prior hospitalization.